Investigation of Physicho-chemical Properties and Characterization of Produced Biosurfactant by Selected Indigenous Oil-degrading Bacterium - Ziba NAJMI; Gholamhossein EBRAHIMIPOUR; Andrea FRANZETTI; Ibrahim Mohamed BANAT (Tehran University of Medical Sciences, 2018)
Background: Due to the amphipathic properties of biosurfactants which act on surfaces and interfaces interest by a variety of industries such as cosmetic, pharmaceutical, bioremediation and petroleum-related industries has recently increased. Methods: Detection of a high-efficiency biosurfactant producer using preliminary screening methods from soil contaminated with crude oil was carried at the Microbiology Laboratory at Shahid Beheshti University, Tehran, Iran in 2013. Then after characterization of some physico-chemical properties of produced biosurfactant and production optimization conditions, processes of purification and complete identification were done. Results: Pseudomonas aeruginosa sp. ZN was selected as high-efficiency biosurfactant producing strain from soil contaminated with oil from Ahvaz City, Khuzestan Province, southern Iran. The biosurfactant production in modified BH2 culture medium supplemented with 1% n-hexadecane occurred during exponential phase resulting in a reduction surface tension from 70 to 29 mN/m. Strain ZN produced biosurfactant with different properties to other Pseudomonas reported. These characterizations included continued production at C/N ratio range of 10-40; the produced biosurfactant could not separate stable emulsion of span-80-kerosene: Tween-80-distilled water (30:70) within 24 h. The produced biosurfactants were able to increase hydrophobicity of bacterial cell to 55%. Recovery of biosurfactants from cell-free supernatant was performed with acid precipitation and ammonium sulfate precipitation. Chemical analysis such as spraying techniques on developed TLC plate and staining methods of supernatant indicated that produced biosurfactants were glycolipids, characterized by ESI-MS analysis of extracted product as di-rhamnolipids. Conclusion: Ability of this strain to produce biosurfactant in the presence of cooked oil and n-hexadecane make it an optimistic candidate for biodegradation of some derivatives of crude oil and food industry.